THE RELEVANT COSTING CONCEPT FOR INCOME MEASUREMENT–CAN IT BE DEFENDED? - Fess, Philip E. (The Accounting Review, 1963)
Abstract The article examines the concept of relevant costing for income measurement and evaluates its merits as a generally accepted concept guiding the reporting to the external users of financial data. Accounting is primarily concerned with providing interested parties with the most useful information possible about the financial activities of a specific enterprise. The reports evolving from the accounting process are useful in the conservation, increase and effective use of the material resources of the enterprise. In this role accounting finds itself in the awkward position of having to provide useful information to many different users to be used for many different purposes. One of the most recent concepts to be set forth as a guide in reporting to the external users of financial statements is relevant costing. Relevant costing has been proposed as an addition to generally accepted accounting concepts for inventory evaluation in published financial statements. The proposal of relevant costing should be met by a careful analysis of the theory underlying the concept. If this new concept is theoretically sound, the accounting profession should consider it as an addition to acceptable accounting.